Relationship between family functioning and self-transcendence in patients with breast cancer: A network analysis - He, Chunyan; Yang, Tianqi; He, Yang; Guo, Sijin; Lin, Yawei; Wu, Chao; Gao, Li; Liu, Xufeng; Wu, Shengjun; Cao, Baohua (Frontiers in Public Health, 2022)
Abstract Background: For patients with breast cancer, family functioning is an important factor affecting self-transcendence, which is a key source of happiness. Purpose: The present study investigated the network structure of family functioning and self-transcendence in patients with breast cancer and aimed to identify bridge items to provide suggestions for the improvement and intervention of self-transcendence in patients with breast cancer. Methods: A total of 294 patients with breast cancer were enrolled in our study. Self-transcendence was evaluated with the Self-Transcendence Scale. Family functioning was evaluated with the Family Adaptation, Participation, Growth, Affection, Resolution (APGAR) Scale. SPSS 25.0 software was used to analyze descriptive data, and R 4.1.1 software was used to construct the network model and calculate the bridge centrality indices. Results: In the network, different aspects of family functioning were positively correlated with different self-transcendence contents. There were 22 edges across communities. The strongest correlation of “Adaptation” was with “Enjoyment of hobbies”. The strongest correlation of “Participation” was with “Life enjoyment”. The strongest correlation of “Growth” was with “Acceptance of bodily changes”. The strongest correlation of “Affection” was with “Life enjoyment”. The strongest correlation of “Resolution” was with “Help acceptance”. “Adaptation” had the highest bridge expected influence value (0.30) in the family functioning community, while “Life enjoyment” had the highest bridge expected influence value (0.27) in the self-transcendence community. Conclusion: Complex patterns of associations existed in the fine-grained relationship between family functioning and self-transcendence in patients with breast cancer, and different aspects of family functioning were linked with self-transcendence through distinct pathways. From the perspective of network analysis, the “Adaptation” aspect of family functioning and the “Life enjoyment” aspect of self-transcendence may be the best targets for improving self-transcendence.